The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/hep.26628
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest and DNA damage 45G down-regulation contributes to janus kinase/signal transducer and activator of transcription 3 activation and cellular senescence evasion in hepatocellular carcinoma

Abstract: Growth arrest and DNA damage 45G (GADD45G), a stress sensor with multiple implications in various biological processes, is down-regulated in a broad spectrum of cancers. However, little is known about the biological effects of GADD45G on hepatocellular carcinoma (HCC) cells and the related mechanisms. In the present study, we found that GADD45G was commonly down-regulated in oncogene-transformed mouse liver cells and in human and mouse HCC. Ectopic expression of GADD45G robustly elicited senescence in HCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…The knockdown of Shp2 efficiently counteracts GADD45G‐induced senescence. In clinical HCC specimens, GADD45G expression is inversely correlated with phosphorylated Stat3 expression in tumour cells and disease progression ; this result was consistent with the relationship of Shp2 with Stat3 .…”
Section: Functions Of Shp2 In Cancerssupporting
confidence: 80%
“…The knockdown of Shp2 efficiently counteracts GADD45G‐induced senescence. In clinical HCC specimens, GADD45G expression is inversely correlated with phosphorylated Stat3 expression in tumour cells and disease progression ; this result was consistent with the relationship of Shp2 with Stat3 .…”
Section: Functions Of Shp2 In Cancerssupporting
confidence: 80%
“…STAT3, a transcription factor that participates in numerous cytokine signaling, has been demonstrated to be constitutively activated by tyrosine phosphorylation in HCC (24). Activation of STAT3 is associated with resistance of tumor cells to chemotherapeutic agents (25), and the downregulation of STAT3 is able to overcome chemoresistance (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the present authors demonstrated that NAC1 negatively regulates the expression of GADD45GIP1 (6) and GADD45G (4). Additionally, Zhang et al (15) recently demonstrated that GADD45G promotes cellular senescence in hepatocellular carcinoma (HCC) cells and markedly suppresses tumor growth in vivo . It was demonstrated that GADD45 G induces HCC cell senescence independently of the functional presence of p16, p53 and retinoblastoma protein and that downregulation of Janus kinase (Jak)/signal transducer and activator of transcription 3 (Stat3) is the key event for GADD45G-induced cell senescence and tumor suppression.…”
Section: Discussionmentioning
confidence: 99%